The history of the formation of folk choirs, vocal and choreographic ensembles in the 1940s and 1950s: Ukrainian and Polish context - Zlochevska, Yuliya (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2024)
The relevance of the study. In the 40s and 50s of the twentieth century, cultural policy in both Ukraine and Poland was characterised by the growing pressure of the Soviet government on culture, the spread of utilitarianism and a propagandistic understanding of art. Exactly at such moments of crisis, society begins to look for a common ground on which each of its members could rely, something that could unite people, remind them of values as the basis of the existential selfdetermination of the individual and the nation. Returning to one’s own roots through the activities of ensembles is one of these paths. This was one of the reasons for the development of choral art as an aspect of state strategy at that time. In addition, this method allowed the government to levelling the identity of the various nationalities that were part of the USSR. The formation of choral music was determined by state support for cultural projects. However, it should be pointed out that the activities of these collectives played an important role in the formation of the national choral school. The main objective of the study is to determine how the process of formation of folk choirs as well as vocal and choreographic ensembles took place in the 1940s and 1950s and to present a comparative analysis of the activities of two ensembles: Grigoriy Veryovka Ukrainian National Honoured Academic Folk Choir and The Stanisław Hadyna Song and Dance Ensemble «Śląsk», which will allow us to consider the problem from two perspectives: Ukrainian and Polish. The methodology includes a critical analysis of literary and historical sources, the method of the history of ideas (to trace the idea of creating academised folk melody-based ensembles that belonged to the official art in the period of the 1940s and 1950s in two different countries), the comparative method (to identify common and distinctive artistic and aesthetic principles of the ensembles‘ activities), and the complex method (to study the problem of the formation of professional folk ensembles in the mid-twentieth century in a holistic way). Results and conclusions. In conclusion, it can be stated that in both Ukraine and Poland, music of the twentieth century developed under the conditions of Soviet ideological pressure. Accordingly, the functioning of the ensembles was integrally connected with the historical, political, social, and cultural circumstances and realities of that time, which influenced not only the repertoire policy, intensive concert activity, but also the artistic style created.Therefore, in the Ukrainian concept, more emphasis was placed directly on the academic nature of singing and author’s arrangements of folk songs. It is worth emphasising that the activities of the Ukrainian National Honoured Academic Folk Choir under the direction of Grygoriy Verevka as an academic official art form are a significant contribution to the development of professional folk choral performance, as well as to the professionalisation of choral education and the establishment of a national choral school, despite the presence of ideological elements in the repertoire. On the other hand, in Poland, and especially in Cieshyn Silesia, the ensemble was initially based on traditional culture - one of the key positions in the development of the Polish ensemble was the collection and presentation of various types of Polish folk songs and dances. At the same time, there was a process of attracting ideas of alternative spirituality, searching and creating new ideas, original artistic formulas that had not previously been present in the work of other Polish ensembles, and as a result, a new cultural perspective based on tradition but open to large-scale changes was created. The prospects for further research on this issue include the detailed study of the creative heritage of the founders of ensembles, the detection and analysis of all periods of the ensembles’ activity with a focus on the present, and the identification of changes in the consciousness of national identity that occurred in the context of the history of the formation of these ensembles.